ON THE PHYSIOLOGICAL PREREQUISITES AND FUNDAMENTAL AXIOMS OF THINKING (Experimental biology, 2021)
Human memory functions on several levels. Primary is directly related to sensory imprinting and is localized in the thalamus. Human thinking is based on long-term memory and is formed in the areas immediately adjacent to the corresponding sensory analyzers in the cerebral cortex. Formal logic is a science investigating the basic axioms and principles of thinking; its conceptual apparatus reflects an idealization of multiple working structures and contacts existing in the cortex.In this theoretical research the author has comprehensively studied a qualitatively new conception of human thinking and memory based on the principles of psycholamarkism, neovitalism and system-evolutionary hierarchy. A special role in these processes is assigned to histone proteins and astrocytes. According to the author, astrocytes act as passive memory keepers, which carry an analog rather than digital code, closely interacting through biochemical connections between glio- and neurotransmitters.            In addition, a separate line is also written about the still hard-to-explain abilities of some terrestrial unicums to hypercalculus and other miraculous mnemonic phenomena. The last section describes five fundamental principles and axioms of thought.
Keywords: evolution of the mind; astrocytes; histones; informons; system hierarchy; hierarchical continuity of memory; holistic monadic perception